Gender, leadership orientation, and effectiveness: testing the theoretical models of Bolman & Deal and Quinn. - Thompson, Michael D. (Sex Roles, 2000)
This study examined the differences in gender between a “balanced” or “unbalanced” orientation of leadership, leadership characteristics, and the perceived effectiveness of educational leaders through subordinate responses in the context of Bolman and Deal's (1991, 1997) four-frame leadership theory and Quinn's (1988) competing values model. The findings suggests that any difference in the perceived effectiveness of educational leaders in the three leadership type groups are equally true for male and female leaders, and that male and female educational leaders were perceived to be equally effective in their respective organizations despite the stereotypical connotations asserted in previous research. In addition, no significant differences were found between men and women in their leadership characteristics, which stands in contrast to extant research-supported evidence. This study analyzed the ratings of 57 leaders (males = 31; females = 26) by 472 subordinate participants (males =234; females = 238) from lower, middle, and upper management levels in secondary and postsecondary institutions. Approximately 60% of the participants and one third of the educational leaders were African Americans. Reprinted by permission of the publisher.